Modernity/Modernism in Philippine Literature - Maria Louisa Torres Reyes (Universitas Sanata Dharma, 2014)
When the American colonial regime set up the Philippine public school system in the first decade of 1900s, it installed a curriculum that was heavily based on the American educational system. The English literature and humanities curriculum, in particular, was heavily Anglo-American notwithstanding the Filipinos lack of proficiency in the English language in the early years. By the third decade of the American occupation, the Filipinos who had been able to attend the university in the country and abroad and had developed a higher level of competence in the English language, began to produce writers and critics who had been trained formally in the Anglo-American literary and critical modes. This generation produced the first Filipino modernist writers, who would later constitute the canon of Philippine Literature. Soon after, Filipino writers in Tagalog and the other Philippine languages began to develop a taste for modernist writing as well and soon produced their own kind of modernistas. Ironically, as Americanization in literature developed inroads in Philippine letters in the major languages, Filipino writers in English and Philippine languages, specifically, were to be split into two camps, the art for arts sake camp (the modernists), led by Jose Garcia Villa, and the socially oriented camp (the socially oriented writers) led by Salvador P. Lopez. The first claimed to be heir to Anglo-Americanmodernist writers whose works they had read; the second were said to be heir to the local tradition of socially-oriented writings in Philippine literature which tradition they ostensibly wished to keep alive. Numerous polemical exchanges would ensue from the 1900s to the 1940s shortly before World War II, which were published in the daily newspapers and weekly magazines. The polemics would embody the contradictions as well as the ambivalences of the Filipino writers reception of AngloAmerican literary modernism, outline the contours of modernism in Philippine literature, and underscore the continuing unease that Filipino writers today, especially those writing in Philippine languages, about western modernism, and the desire to go past it, resulting in the development of a complex if contradictory kind of modernism and a sense of modernity and the role of language in this development. Key words: modernity, modernism, Philippine literature